A review of the stratigraphic characteristics and age data of the main rock units in the Bor Metallogenic Zone (Timok Magmatic Complex) - Banješević M. (Journal of Mining and Metallurgy. Section A: Mining)
This study reports on the stratigraphic characteristics of the main units and indicates the link between magmatism and mineralization in the Bor Metallogenetic Zone (BMZ)-the Timok Magmatic Complex (TMC). Existing data are supplemented by the latest different systematic long-term geological and stratigraphic surveys and new and contemporary mineral exploration methods. The TMC extends on a continental crust composed of different types of the Proterozoic to the Lower Cretaceous units and consists of the volcanic/magmatic, volcanogenic-sedimentary and sedimentary rock packages. Sedimentary processes and magmatism were almost continuous throughout the Late Cretaceous. The sedimentation lasted from the Albian-Cenomanian to the Maastrichtian. Magmatism occurred in at least two phases from the Upper Turonian to the Upper Campanian: I volcanic phase-V1 (90-82 Ma), II volcanic phase-V2 (83-78 Ma), with a steady decrease in age from East to West. Cu-Au porphyry mineralization occurs between 87-80 Ma. The major epithermal and porphyry mineralization is related to the V1 magmatic phase predominantly developed in the easternmost part of the BMZ.